Traumatic esophageal perforation in a premature infant - Tekant, Gonca; Abbasoğlu, Latif; Sever, Nihat; Bulut, Melih (The Turkish Journal of Pediatrics, 1990)
We presented a case of neonatal hypopharyngeal perforation resulting from extraction of a breech presentation, with symptoms of regurgitation at all feedings and excessive salivation. Inability to pass a nasogastric tube suggested the diagnosis of esophageal atresia. The diagnosis and treatment of this condition is discussed, and the literature is reviewed.
Keywords: neonate; esophagus; hypopharynx perforation